Health utilities and quality-adjusted life years for patients with amyotrophic lateral sclerosis receiving reldesemtiv or placebo in FORTITUDE-ALS. (31st December 2023) - Gebrehiwet, Paulos; Meng, Lisa; Rudnicki, Stacy A.; Sarocco, Phil; Wei, Jenny; Wolff, Andrew A.; Butzner, Michael; Chiò, Adriano; Andrews, Jinsy A.; Genge, Angela; Hughes, Dyfrig A.; Jackson, Carlayne E.; et al.
Abstract: Aims: To estimate the health utilities and quality-adjusted life years (QALYs) in patients with amyotrophic lateral sclerosis (ALS) receiving reldesemtiv versus placebo in FORTITUDE-ALS. Materials and methods: We performed a post hoc analysis of clinical trial data from FORTITUDE-ALS (NCT03160898). This Phase IIb, double-blind, randomized, dose-ranging, placebo-controlled, parallel-group, 12-week trial evaluated reldesemtiv in patients with ALS. Health utilities from the five-level version of the EuroQol five-dimensional questionnaire (EQ-5D-5L) were estimated using ALS Functional Rating Scale-Revised (ALSFRS-R) scores collected during the trial. QALYs were estimated using the area under the curve method. Results: The full analysis set consisted of 456 patients ( reldesemtiv n = 342, placebo n = 114), who received at least one dose of the double-blind study drug, and had ALSFRS-R assessed at baseline and at least one post-baseline assessment. The difference in EQ-5D-5L utility least-squares (LS) mean change from baseline to week 12 for reldesemtiv versus placebo, adjusted for baseline values, was statistically significant (0.03, 95% confidence interval [CI]: 0.01, 0.05; p = .0008). The incremental QALY of reldesemtiv versus placebo adjusted for baseline utility values showed a modest, but statistically significant, difference (0.004, 95% CI: 0.001, 0.007; p = .0058). Conclusions: This post hoc analysis of FORTITUDE-ALS suggests that reldesemtiv showed a modest but significant benefit in health utilities and QALYs compared with placebo. Future long-term studies that include direct collection of EQ-5D-5L data will be needed to confirm our findings. ClinicalTrials.gov identifier: NCT03160898